Faunistic analysis of the caridean shrimps inhabiting seagrasses along the NW coast of the Gulf of Mexico and Caribbean Sea - Barba Macías, Everardo (2012)
Seagrass meadows are highly productive and ecologically important habitats in estuaries and coastal lagoons, and contain a variety of faunal communities, from which the caridean shrimps are a dominant component. The purpose of this work was to analyze the environmental parameters of water and sediments, with the biological components in seagrass epifaunal communities, from the Western Gulf of Mexico and the Caribbean Sea. For this, density and diversity of caridean shrimps were analyzed and correlated with environmental parameters and seagrass biomass, and zoogeographic affinities were determined. The spatial distribution of caridean shrimps was recorded for 12 localities with Halodule wrightii and Thalassia testudinum monospecific seagrass meadows. A total of 72 158 individuals of 16 taxa were collected. Among results, the Hippolytidae resulted the most abundant group (92.3%) with eight species, and was followed by Palaemonidae with 7.6% of the abundance and seven species, and the Alpheidae with only one genus. From the total of collected carideans, a 37.3% was found in H. wrightii and 62.7% in T. testudinum. The dominant species were Hippolyte zostericola (12.39ind./m2), Tozeuma carolinense (9.5ind./m2), Thor dobkini (4.84ind./m2) and Palaemonetes vulgaris (4.87ind./m2). The zoogeographic distribution of the carideans presented two groups: species of the Virginian-Carolinean province representing its Southern limit (43.75%) and species of the Brazilian-Caribbean province representing its Northern limit (56.25%). The species H. zostericola, T. carolinense, P. vulgaris, P. pugio and P. intermedius are widely distributed along the Western Atlantic coast. This study has base line information for seagrass habitats, the community of epifaunal carideans and their ecological affinities, previous to the oil spill in the Gulf of Mexico.